Bee-Inspired Healing: Apitherapy in Veterinary Medicine for Maintenance and Improvement Animal Health and Well-Being - Jevrosima Stevanović; Uroš Glavinić; Marko Ristanić; Vladimira Erjavec; Barış Denk; Slobodan Dolašević; Zoran Stanimirović (MDPI AG, 2024)
This review aims to present current knowledge on the effects of honey bee products on animals based on in vivo studies, focusing on their application in clinical veterinary practice. Honey's best-proven effectiveness is in treating wounds, including those infected with antibiotic-resistant microorganisms, as evidenced in horses, cats, dogs, mice, and rats. Propolis manifested a healing effect in numerous inflammatory and painful conditions in mice, rats, dogs, and pigs and also helped in oncological cases in mice and rats. Bee venom is best known for its effectiveness in treating neuropathy and arthritis, as shown in dogs, mice, and rats. Besides, bee venom improved reproductive performance, immune response, and general health in rabbits, chickens, and pigs. Pollen was effective in stimulating growth and improving intestinal microflora in chickens. Royal jelly might be used in the management of animal reproduction due to its efficiency in improving fertility, as shown in rats, rabbits, and mice. Drone larvae are primarily valued for their androgenic effects and stimulation of reproductive function, as evidenced in sheep, chickens, pigs, and rats. Further research is warranted to determine the dose and method of application of honey bee products in animals.